Design and analysis of a non-uniform planar antenna array - Sahad, Asif Jamil; Islam, Md Shazzadul; Islam, Md Rafiqul; Asadullah, G M; M Adnan, Noor Hidayah (IEEE, 2020)
A 2 x 2 non-uniform planar array with a new technique of array arrangement has been proposed in this paper. The proposed non-uniform array has been achieved by shifting the second-row elements with a change of certain angle with respect to the elements in the first row. After optimizing the angle using CST MWS, the proposed array has achieved a peak realized gain of 12.06 dB with the highest radiation efficiency of 88.26% at 5.8 GHz. New non-uniform array configuration has achieved a low sidelobe level of – 23.1 dB by reducing the mutual coupling effect. A high directivity of 12.61 dBi with more than 20.5 dB isolation at the resonate frequency and – 37 dB minimum return loss makes it suitable for high data rate MIMO applications. Moreover, the size of the array can also be extended to a large array with a flexible shape.